Neuroendocrine tumours of the stomach – analysis of 3 cases - Kula, Zbigniew; Weishof, Alicja; Świątczak, Czesław (Contemporary Oncology/Współczesna Onkologia, 2006)
Gastric neuroendocrine tumours account for 8.7% of all gastrointestinal neuroendocrine tumours (GEP NET). Three types of tumours may be distinguished on the basis of background gastric pathology: type I, which develops in atrophic body gastritis; type II, which is associated with multiple endocrine neoplasia and Zollinger-Ellison syndrome; and sporadic type III, which is not associated with any background pathology. This classification plays a major role in determining the optimal approach to these diseases. The study presents 3 patients with NET of the stomach. Two of the patients were diagnosed to have type I of gastric carcinoid and one patient – type III of gastric carcinoid (sporadic). The clinical diagnosis of NET was confirmed by gastroscopy and histopathological examination. Attention was paid to distinguish between the two first types of gastric NET and the type III.